From Digital Divide to Technostress during the COVID-19 Pandemic: A Scoping Review - Seberini Andrea; Nour Magde Mohamed; Tokovska Miroslava (Organizacija, 2022)
Background and purpose: This paper relates challenges faced by older adult employees during the COVID-19 crisis in order to describe strategies to reduce the digital divide and technostress, thereby supporting inclusion and retention in the marketplace. Older adults are particularly at risk of Internet-related social exclusion, especially during the COVID-19 pandemic. The main research question of the current scoping review were: What kind of strategies can reduce the digital divide and technostress of older adult employees and contribute to their inclusion and retention in the working market during the COVID-19 pandemic?